Influence of Weight Gain Rate on Early Life Nutritional Status and Body Composition of Children - Sarah Aparecida Vieira; Taís Cristina Araújo Magalhães; Andréia Queiroz Ribeiro; Silvia Eloiza Priore; Sylvia do Carmo Castro Franceschini; Luciana Ferreira da Rocha Sant’Ana (The Scientific World Journal)
Objective. To evaluate the influence of the weight gain rate at 4–6 months on nutritional status and body composition in children between 4 and 7 years of age. Methods. Retrospective cohort study, sample of 257 children. Data collection was performed in two stages, with the first relating to retrospective data of weight gain from birth to the first 4–6 months of life in the patient records. Measurements of weight, height, waist circumference, and body composition in children between ages 4 and 7 years were obtained. Nutritional status was assessed by the BMI/age. Control variables, such as pregnancy, breastfeeding, lifestyle, and sociodemographics, were studied. Descriptive analysis and multiple linear regression were performed. Results. In the nutritional status assessment, the prevalence of overweight observed was 24.9%. After adjusting for control variables, it was found that the increase of the WGR at 4–6 months of age explained the occurrence of higher BMI/age, percentage of total body fat, body fat percentage in the android region, and waist circumference in children between 4 and 7 years of age. Conclusion. The increase of the WGR in the first months of life can lead to the occurrence of higher values of parameters of nutritional status and body composition in later life.